Comparison of spontaneous resolution of secundum atrial septal defects in term and preterm neonates - Imtiaz Ahmad; Tanveer Ahmad; Imran Khan; Raheela Mukhtar (Journal of University Medical & Dental College, 2025)
BACKGROUND & OBJECTIVE: Atrial septal defects (ASDs) are among the most common congenital heart defects, with secundum ASDs accounting for approximately 70% of cases. These often close spontaneously during infancy or early childhood. However, the timing and likelihood of spontaneous closure may be influenced by gestational age. This study aimed to compare the spontaneous resolution of secundum ASDs in term versus preterm neonates and to identify potential predictors for natural closure to guide optimal early interventions.METHODOLOGY: This cohort study was conducted at the Pediatric Department of Hilal-e-Ahmar Hospital, Faisalabad, Pakistan, from December 2022 to March 2024. A total of 280 neonates were enrolled—140 preterm and 140 term—each diagnosed with a secundum ASD within one month of birth. Newborns with major congenital heart defects were excluded. Patients were followed until spontaneous resolution, defined as defect closure or reduction in size to less than 3 mm without the need for medical or surgical intervention.RESULTS: The mean age at baseline and follow-up was 4.44±1.86 days and 13.57±6.56 months for term neonates, and 8.11±5.68 days and 14.16±6.87 months for preterm neonates. Among preterms, 55% were male and 45% female; among terms, 51.4% were male and 48.6% female. While most ASDs resolved spontaneously in both groups, resolution was less frequent among preterm infants.CONCLUSION: Spontaneous resolution of secundum ASDs is common in both term and preterm neonates, though preterm infants show a lower rate of closure. Early identification and follow-up are essential for optimizing outcomes.